2022
DOI: 10.1007/s11606-022-07801-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cost-Related Considerations on Clinical Trial Participation: Results from the 2020 Health Information National Trends Survey (HINTS)

Abstract: Background People experiencing financial burden are underrepresented in clinical trials . Objective Describe the prevalence of cost-related considerations influential to trial participation and their associations with person-level characteristics. Design This cross-sectional study used and assessed how three cost-related considerations would influence the decision to participate in a hypothetical clinical trial. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Our previous study of >3500 US adults nationwide found that respondents with lower perceived income had double the odds of reporting a cost‐related consideration as very influential to clinical trial participation than those with higher perceived income, even after accounting for patient age, race, and residence 18 . However, respondents from this study were disease‐agnostic and were considering hypothetical clinical trial participation.…”
Section: Introductionmentioning
confidence: 51%
See 1 more Smart Citation
“…Our previous study of >3500 US adults nationwide found that respondents with lower perceived income had double the odds of reporting a cost‐related consideration as very influential to clinical trial participation than those with higher perceived income, even after accounting for patient age, race, and residence 18 . However, respondents from this study were disease‐agnostic and were considering hypothetical clinical trial participation.…”
Section: Introductionmentioning
confidence: 51%
“…Our previous study of >3500 US adults nationwide found that respondents with lower perceived income had double the odds of reporting a cost‐related consideration as very influential to clinical trial participation than those with higher perceived income, even after accounting for patient age, race, and residence. 18 However, respondents from this study were disease‐agnostic and were considering hypothetical clinical trial participation. Little is known about trial‐related financial hardship, defined as high out‐of‐pocket costs and accompanying financial distress, 19 and its impact on patients with financial barriers to care considering or participating in cancer‐specific clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…Covariates included in this study were informed by prior literature delineating factors associated with clinical trial knowledge and participation. 5,8 The specific sociodemographic variables and health-related variables included in this study were age (18-34 years, 35-49 years, 50-64 years, and 65 years or older), sex, race/ethnicity (White, Black or African American, Hispanic, and others), educational level (high school graduate or less, some college, college graduate, and postgraduate), marital status, household income (less than US$20k, US$20k to less than US$35k, US$35k to less than US$50k, US$50k to less than US$75k, and US$75k or above), having a regular provider, presence of comorbidities (one or more of the following conditions: diabetes mellitus, hypertension, heart disease, lung disease, or previous cancer diagnosis), and rural-urban residence.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have documented racial, economic, individual, and geographic disparities in clinical trial participation. [5][6][7][8][9][10] This discrepant inclusion of certain sub-populations may widen already existing health disparities among underserved populations. Thus, efforts to increase diverse participation in clinical trials in the United States are warranted.…”
Section: Introductionmentioning
confidence: 99%